Microarchitectural Changes of Cardiovascular Calcification in Response to In Vivo Interventions Using Deep-Learning Segmentation and Computed Tomography Radiomics. Issue 8 (16th June 2022) - Patel, Nikhil Rajesh; Setya, Kulveer; Pradhan, Stuti; Lu, Mimi; Demer, Linda L.; Tintut, Yin
Abstract : Background: Coronary calcification associates closely with cardiovascular risk, but its progress is accelerated in response to some interventions widely used to reduce risk. This paradox suggests that qualitative, not just quantitative, changes in calcification may affect plaque stability. To determine if the microarchitecture of calcification varies with aging, Western diet, statin therapy, and high intensity, progressive exercise, we assessed changes in a priori selected computed tomography radiomic features (intensity, size, shape, and texture). Methods: Longitudinal computed tomography scans of mice ( Apoe −/− ) exposed to each of these conditions were autosegmented by deep learning segmentation, and radiomic features of the largest deposits were analyzed. Results: Over 20 weeks of aging, intensity and most size parameters increased, but surface-area-to-volume ratio (a measure of porosity) decreased, suggesting stabilization. However, texture features (coarseness, cluster tendency, and nonuniformity) increased, suggesting heterogeneity and likely destabilization. Shape parameters showed no significant changes, except sphericity, which showed a decrease. The Western diet had significant effects on radiomic features related to size and texture, but not intensity or shape. In mice undergoing either pravastatin treatment or exercise, the selected radiomic features of their computed tomography scans were not significantly different from those of their respective controls. Interestingly, the total number of calcific deposits increased significantly less in the 2 intervention groups compared with the respective controls, suggesting more coalescence and/or fewer de novo deposits. Conclusions: Thus, aging and standard interventions alter the microarchitectural features of vascular calcium deposits in ways that may alter plaque biomechanical stability.